Sexuality is not a priority when disease and treatment side effects are severe: conceptions of patients with malignant blood diseases. Issue 23 (5th September 2013) - Olsson, Cecilia; Athlin, Elsy; Sandin‐Bojö, Ann‐Kristin; Larsson, Maria
Abstract : Aims and objectives: To describe how patients with malignant blood diseases conceive the influence of chemo‐ or chemoimmunotherapy on sexuality, and their need of support related to this issue. Background: Sexuality is often negatively affected in cancer patients with sex‐specific diagnoses. For patients with malignant blood diseases, the research is limited with regard to the effect on sexuality. Knowledge about their need for support related to sexuality is also needed as nurses are found to often avoid this area of their responsibility. Design: Qualitative design. Methods: Twelve patients treated for malignant blood diseases were interviewed twice. Phenomenography was used for the analysis. Results: The analyses revealed an outcome space consisting of two main categories: 'Sexuality is overshadowed by the cancer experience' and 'No need of support but timely information might be helpful', both comprehensively related to three interrelated description categories 'Affected strength', 'Affected sexual desire' and 'Affected body image', which describe conceptions of how sexuality was affected. Conclusion: Patients experienced negative effects on sexual function and sexual relationship during and after treatment period due to affected strength, sexual desire and negatively body image. However, when disease and side effects were experienced as severe, thoughts and interest of sexuality were overshadowed, and the need or wish for support related to this issue was very low. It is important to note that some patients expressed that pre‐ or post‐treatment information might have been helpful. Relevance to clinical practice: It is acknowledged in the cancer care of today that cancer follow‐up should address psychosocial support in which sexuality is an important area. Therefore, it is imperative that cancer care is organised in a patient centred way, with adequate time for nurses to provide continuity in the nurse–patient relation and supportive care also during cancer rehabilitation.